Prevalence and Outcomes of Unilateral Versus Bilateral Oophorectomy in Women With Ovarian Cancer: A Population-Based Study - Xiong, Jiaqiang; Zhang, Zhuoqun; Liu, Yanyan; Fan, Guanlan; Wu, Kejia; Zhang, Wei (Frontiers in Oncology, 2022)
Background: Unilateral oophorectomy has the benefits of preserving the ovarian function of fertility and hormone secretion, but the precise inclusion criteria for candidates for this procedure remain controversial. This study aimed to compare the prevalence and therapeutic efficiency of unilateral oophorectomy in women with ovarian cancer who underwent bilateral oophorectomy; moreover, it aimed to identify the appropriate candidates for unilateral oophorectomy. Methods: Female patients diagnosed with stage I-III ovarian cancer between 2000 and 2017 were retrospectively identified from the Surveillance, Epidemiology, and End Results program database. Overall survival (OS) and disease-specific survival (DSS) after unilateral or bilateral (salpingo-) oophorectomy were estimated. Cumulative mortality rates (CMRs) for non-cancer comorbidities were also estimated. Results: A total of 28,480 women with ovarian cancer were included in this study, of whom 11,517 died during the study period. Of the patients, 7.5% and 48.0% underwent unilateral and bilateral oophorectomy, respectively. Overall, for stage-Ia tumors, unilateral oophorectomy was associated with remarkably better OS and DSS than bilateral oophorectomy (OS: p < 0.001; DSS: p = 0.01). For stage-Ib and stage-Ic ovarian tumor, there was no significant difference between the OS and DSS of patients treated by unilateral oophorectomy and those treated by bilateral oophorectomy. For stage-II and stage-III ovarian cancer, unilateral oophorectomy was associated with remarkably worse OS and DSS than bilateral oophorectomy. Among the reproductive-age women younger than 50 years, the OS and DSS of patients with stage-I tumors receiving unilateral oophorectomy were comparable to those receiving bilateral oophorectomy, even for high-grade stage-Ic tumors (all p > 0.05). For those aged 50 years and older, OS and DSS of patients with stage-I tumor receiving unilateral oophorectomy were significantly worse than those receiving bilateral oophorectomy, even for low-grade stage-Ia ovarian tumor (OS: p < 0.001; DSS: p = 0.02). Conclusion: Unilateral oophorectomy exhibited excellent oncological superiority and was equivalent to bilateral oophorectomy for stage-I ovarian tumors among women of reproductive age. For women of reproductive age, the criteria of unilateral oophorectomy can be appropriately broadened to high-grade stage-Ic diseases because of the better performance of unilateral oophorectomy in this population.